2018
DOI: 10.1159/000487318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Prognostic Homeopathic Questionnaire for Women with Premenstrual Disorders

Abstract: Background/Aims: Validation of treatments with individually prescribed homeopathic medicines is a challenging task. A prognostic homeopathic patient questionnaire containing 140 keynote symptoms (highly characteristic of a specific homeopathic medicine) and an electronic algorithm to process the answers were used in 2 clinical studies. The algorithm outcome, based on total symptom scores, indicated 1 of 11 pre-selected homeopathic medicines for women with premenstrual syndrome and premenstrual dysphoric disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…1.5) was found in 34 keynote symptoms with a prevalence of 10 to 40% and it was concluded that the prognostic questionnaire proved as a reliable tool to rank 11 homoeopathic medicines by total scores, based on keynote symptoms. 11 This series of 15 consecutive cases treated with keynote method is documented for the purpose of generation of valid and acceptable evidence in favour of keynote prescription.…”
Section: Discussionmentioning
confidence: 99%
“…1.5) was found in 34 keynote symptoms with a prevalence of 10 to 40% and it was concluded that the prognostic questionnaire proved as a reliable tool to rank 11 homoeopathic medicines by total scores, based on keynote symptoms. 11 This series of 15 consecutive cases treated with keynote method is documented for the purpose of generation of valid and acceptable evidence in favour of keynote prescription.…”
Section: Discussionmentioning
confidence: 99%
“…'Homeopathic' prognostic factors can be useful for designing targeted (semi-)individualised homeopathic treatment plans for clinical research, as was recommended from additional analysis of a clinical study on premenstrual syndrome. 31 Additionally, quantitative analysis could be performed. With Bayes' theorem, the prognostic value of a keynote symptom can be assessed, predicting therapeutic success with a specific (individually prescribed) homeopathic medicine.…”
Section: Case Collectionmentioning
confidence: 99%